2014
DOI: 10.1080/00405000.2014.988436
|View full text |Cite
|
Sign up to set email alerts
|

Study on compressional energy contribution into total energy of pile deformation in cut-pile carpet

Abstract: Compression behavior is one of the most important properties of the carpets. In this study, a new theoretical model has been presented in which total energy of pile deformation in cut-pile carpet including bending energy of pile deformation, frictional loose energy due to sliding pile yarns, and compressional energy due to piles jamming at the end of pile deformation process has been calculated. Then, derived equations have been solved by computer software and calculated theoretical values have been compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This included the bending energy resulting from pile deformation, the energy loss due to sliding pile yarns causing friction, and the energy associated with piles getting jammed at the end of the deformation process. It was found that bending energy was significant compared to frictional and jamming components [ 60 , 61 ]. In their work, Hersh and El-Shiekh (1972) presented a mechanical model to analyze the bending deformation of piles.…”
Section: Introductionmentioning
confidence: 99%
“…This included the bending energy resulting from pile deformation, the energy loss due to sliding pile yarns causing friction, and the energy associated with piles getting jammed at the end of the deformation process. It was found that bending energy was significant compared to frictional and jamming components [ 60 , 61 ]. In their work, Hersh and El-Shiekh (1972) presented a mechanical model to analyze the bending deformation of piles.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, carpet deformation mechanism under compression load has been explored and theoretical-analytical models have been introduced to describe carpet compression behavior. 10,11,14,29 In these studies, physical and mechanical properties of pile yarn and geometrical parameters of carpet structure (such as pile density, pile height, yarn linear density, filament yarn structure, pile fiber material, fibers blend ratio, and pile fiber cross-section shape) have been introduced as factors influencing carpet compression behavior.…”
Section: Introductionmentioning
confidence: 99%